2017
DOI: 10.1186/s12974-017-0906-6
|View full text |Cite
|
Sign up to set email alerts
|

A systems pharmacology-based approach to identify novel Kv1.3 channel-dependent mechanisms in microglial activation

Abstract: BackgroundKv1.3 potassium channels regulate microglial functions and are overexpressed in neuroinflammatory diseases. Kv1.3 blockade may selectively inhibit pro-inflammatory microglia in neurological diseases but the molecular and cellular mechanisms regulated by Kv1.3 channels are poorly defined.MethodsWe performed immunoblotting and flow cytometry to confirm Kv1.3 channel upregulation in lipopolysaccharide (LPS)-activated BV2 microglia and in brain mononuclear phagocytes freshly isolated from LPS-treated mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 64 publications
6
70
0
Order By: Relevance
“…Although published (Charolidi et al 2015; Nguyen et al 2017; Rangaraju et al 2015; Rangaraju et al 2017; Rus et al 2005) and present data clearly showed that in the brain, Kv1.3 is mainly expressed in activated microglia, it has been described in neurons, most prominently in mitral cells of the olfactory bulb (Fadool et al 2004) and presynaptic terminals of brain stem auditory neurons (Gazula et al 2010), and also in cortical interneurons and in oligodendrocyte progenitor cells but at low levels (Vautier et al 2004; Duque et al 2013), raising the possibility that the above in vivo effects of Kv1.3 knockout may be secondary to Kv1.3 hypomorph in neurons. To address this possibility, we used a chemical biology approach, as in neurons Kv1.3 is typically part of hetereomultimers with Kv1.1, Kv1.2 and Kv1.6 subunits (Helms et al 1997) and therefore has a different pharmacology from the Kv1.3 homotetramers or Kv1.3/Kv1.5 heterotetramers found in T cells, microglia and macrophages (Chandy et al 2004; Feske et al 2015; Wulff et al 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although published (Charolidi et al 2015; Nguyen et al 2017; Rangaraju et al 2015; Rangaraju et al 2017; Rus et al 2005) and present data clearly showed that in the brain, Kv1.3 is mainly expressed in activated microglia, it has been described in neurons, most prominently in mitral cells of the olfactory bulb (Fadool et al 2004) and presynaptic terminals of brain stem auditory neurons (Gazula et al 2010), and also in cortical interneurons and in oligodendrocyte progenitor cells but at low levels (Vautier et al 2004; Duque et al 2013), raising the possibility that the above in vivo effects of Kv1.3 knockout may be secondary to Kv1.3 hypomorph in neurons. To address this possibility, we used a chemical biology approach, as in neurons Kv1.3 is typically part of hetereomultimers with Kv1.1, Kv1.2 and Kv1.6 subunits (Helms et al 1997) and therefore has a different pharmacology from the Kv1.3 homotetramers or Kv1.3/Kv1.5 heterotetramers found in T cells, microglia and macrophages (Chandy et al 2004; Feske et al 2015; Wulff et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…A first in vivo suggestion of such a role of Kv1.3 came from a recent report showing that systemic inflammation induced by intravenous administration of LPS to adult mice resulted in increased ShK-F6CA (a fluorescein-conjugated Kv1.3-specific peptide inhibitor) labeling of microglia and infiltrating macrophages in the brain (Rangaraju et al 2017). In the current study, we stereotactically injected LPS into the ventricles (Maezawa et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that Kv1.3 inhibition does not affect phagocytosis in vivo confirming a recent study reporting that Kv1.3 blockers to not impair the ability of isolated brain mononuclear cells to phagocytose polystyrene microspheres. 38…”
Section: Kv13 Blockade Preferentially Reduces Inflammatory Cytokine mentioning
confidence: 99%